Effects of Turbulence on the Combustion Properties of Partially Premixed Flames of Canola Methyl Ester and Diesel Blends. (10th May 2011) - Dhamale, N.; Parthasarathy, R. N.; Gollahalli, S. R.
Abstract : Canola methyl ester (CME) is a biofuel that is a renewable alternative energy resource and is produced by the transesterification of canola oil. The objective of this study was to document the effects of turbulence on the combustion characteristics of blends of CME and No 2 diesel fuel in a partially-premixed flame environment. The experiments were conducted with mixtures of pre-vaporized fuel and air at an initial equivalence ratio of 7 and three burner exit Reynolds numbers, 2700, 3600, and 4500. Three blends with 25, 50, and 75% volume concentration of CME were studied. The soot volume fraction was highest for the pure diesel flames and did not change significantly with Reynolds number due to the mutually compensating effects of increased carbon input rate and increased air entrainment as the Reynolds number was increased. The global NOx emission index was highest and the CO emission index was the lowest for the pure CME flame, and varied non-monotonically with biofuel content in the blend The mean temperature and the NOx concentration at three-quarter flame height were generally correlated, indicating that the thermal mechanism of NOx formation was dominant in the turbulent biofuel flames also.